1971
DOI: 10.1126/science.174.4016.1331
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Nitrogen: Contribution to Nitrate in Surface Water in a Corn Belt Watershed

Abstract: Measurements of nitrate concentration and relative enrichment in nitrogen-15 were made on samples of the surface waters of a typical Illinois corn belt watershed and the effluent of the subterranean tiles that drain the cropped land in the region. From these measurements, we estimate that at the time of peak nitrate concentration in the spring of 1970 a minimum of 55 to 60 percent of the nitrogen found as nitrate in the surface waters of this watershed originated from fertilizer nitrogen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(96 citation statements)
references
References 6 publications
3
90
0
3
Order By: Relevance
“…Biomass accrual has been reported to follow a non-linear increase due to reduced mass transfer velocity, clogged micro channels, detachment by high water velocity, grazing activity and accumulation of toxic substances (SABATER and ADMIRAAL, 2005, and references within). KOHL et al (1971) reported inorganic nitrogen with an isotopic signature of 7.8 ±0.57‰, the upper range for fertilizers, whereas total organic matter was 3.8 ±0.18‰, in agreement with expected values for soil organic nitrogen ( Figure 5). d 15 N-NH 4 + is enriched downstream from the effluent as a result of oxidation, uptake and volatilization; therefore, it is possible that these three processes yield the particular epilithon isotope composition 5700 m downstream from KWTP.…”
Section: Resultssupporting
confidence: 72%
“…Biomass accrual has been reported to follow a non-linear increase due to reduced mass transfer velocity, clogged micro channels, detachment by high water velocity, grazing activity and accumulation of toxic substances (SABATER and ADMIRAAL, 2005, and references within). KOHL et al (1971) reported inorganic nitrogen with an isotopic signature of 7.8 ±0.57‰, the upper range for fertilizers, whereas total organic matter was 3.8 ±0.18‰, in agreement with expected values for soil organic nitrogen ( Figure 5). d 15 N-NH 4 + is enriched downstream from the effluent as a result of oxidation, uptake and volatilization; therefore, it is possible that these three processes yield the particular epilithon isotope composition 5700 m downstream from KWTP.…”
Section: Resultssupporting
confidence: 72%
“…Studies during the 1970s and 1980s largely focused on tracing the fate of fertilizer N in intensive agriculture (e.g. Kohl, Shearer & Commoner, 1971;Meints, Boone & Kurtz, I975fl), and on estimating the fractional contribution of N^-fixation to the N of Na-fixing plants (e.g. Amarger, Mariotti & Mariotti, 1977;Delwiche et al, 1979;Shearer & Kohl, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The legitimacy of tracing of N inputs and outputs has been a major issue of debate within the field of ^^N abundance studies. The debate started with a contribution by Kohl et al (1971) and was immediately followed by a critical remark from Hauck et al (1972, see also reply from Kohl, Shearer & Commoner, 1972), and later more detailed assessments (Edwards. 1973;Focht.…”
Section: Assessment Of N Balances Of Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of 15 N abundances have been used for over 30 years to identify both point and non-point sources of nitrate. Work by Kreitler ( , 1979, Kreitler and Jones (1975), Shearer et al (1978), Kohl et al (1971), Heaton (1986), Mariotti et al (1988), Korom (1992), and Kendall (1998), and others, has contributed to development and use of the method. Examples of a few studies that illustrate the usefulness of the method include Gormly and Spalding (1979) in Nebraska, Mariotti et al (1988) in France, Mitchell et al (2003) in Canada, and Townsend et al (1994) in Kansas.…”
Section: Introductionmentioning
confidence: 99%